2014
DOI: 10.3357/asem.3851.2014
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Analysis of Air Ambulance Blood Product Administration in Combat Operations

Abstract: Potential risks of medical complications, reverse propaganda, adherence to protocol, and diversion and/or wastage of limited resources were important considerations in the development of the pilot program. Aviation-specific risk mitigation strategies were important to ensure mission success in terms of wastage prevention, standardized operations at multiple locations, and prevention of adverse clinical outcomes. Consideration of aviation risk mitigation strategies may help enable other helicopter emergency med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…5256 Finally, position papers from civilian and military thought leaders have been recently published, clearly stating the desire for prehospital blood products and high quality studies to determine their efficacy. 44– 51, 57, 58 In summary, a series of retrospective studies have shown associations with improved outcomes with blood product based resuscitation compared to crystalloid. However a recent comprehensive review of this subject by Smith et al has concluded that there is no effect, albeit the quality of all available data are very low.…”
Section: Discussionmentioning
confidence: 99%
“…5256 Finally, position papers from civilian and military thought leaders have been recently published, clearly stating the desire for prehospital blood products and high quality studies to determine their efficacy. 44– 51, 57, 58 In summary, a series of retrospective studies have shown associations with improved outcomes with blood product based resuscitation compared to crystalloid. However a recent comprehensive review of this subject by Smith et al has concluded that there is no effect, albeit the quality of all available data are very low.…”
Section: Discussionmentioning
confidence: 99%
“…In military services, penetrating injuries were reported by 68% to 100% of studies and the mean or median ISS varied from 15 to 45 (Table ) . The most frequently reported mechanisms of injury were explosions (1%‐87%) and gunshot wounds (13%‐100%) …”
Section: Resultsmentioning
confidence: 99%
“…In military EMS, three observational studies analysed the change in vital parameters after transfusion, all showing improvements (significant rise in SBP and improvement in SI; a fall in HR; or a SBP closer to physiologically normal values as the prehospital transfused volume increased).…”
Section: Resultsmentioning
confidence: 99%
“…Modern helicopter transport teams are equipped with advanced resuscitation measures such as blood products 11. The patient had already received tranexamic acid at the local hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Modern helicopter transport teams are equipped with advanced resuscitation measures such as blood products. 11 The patient had already received tranexamic acid at the local hospital. However, the local hospital had no blood products in stock, and the patient underwent a massive infusion without transfusion, leaving her severely anemic on arrival at our hospital.…”
Section: Uring Interhospital Air Evacuations Wherementioning
confidence: 99%